2021
DOI: 10.22159/ajpcr.2021.v14i10.42822
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antimicrobial Susceptibility Profile of Non Lactose Fermenting Gram-Negative Bacterial Isolates in a Tertiary Care Teaching Hospital of Central India

Abstract: Objectives: The non-lactose fermenting Gram-negative bacilli (NLF-GNB) are notorious pathogens reportedly acquiring multiple drug resistance alarmingly and emerging as a public health threat globally. This study was conducted to isolate and identify these pathogens from clinical samples received routinely in our Bacteriology Laboratory and to analyze their antibiotic susceptibility patterns. Methods: In this cross-sectional study, the first 100 NLF-GNB strains isolated consecutively from 1218 clinical samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
2
1
Order By: Relevance
“…(33%). These isolates in our study showed high resistance to ceftriaxone (83%) as compared to the study by Mehta et al who reported these organisms as sensitive to aminoglycosides and ceftazidime (10).…”
Section: Resultscontrasting
confidence: 50%
“…(33%). These isolates in our study showed high resistance to ceftriaxone (83%) as compared to the study by Mehta et al who reported these organisms as sensitive to aminoglycosides and ceftazidime (10).…”
Section: Resultscontrasting
confidence: 50%
“…The multidrug-resistant E. coli, Klebsiella species, Citrobacter, Pseudomonas aeruginosa and Acinetobacter baumannii showed more resistance against ampicillin, followed by gentamicin, ceftriaxone, ceftazidime, piperacillin and ciprofloxacin [26][27][28][29]33]. The antibiotics like amikacin, and imipenem worked well against all gram-negative multi-drug-resistant organisms in our study about 72%, and 85% respectively except a few isolates of Acinetobacter baumannii and Pseudomonas aeruginosa.…”
Section: Discussionsupporting
confidence: 50%
“…The polymicrobial wound infections with these organisms make eradicating microorganisms more difficult. The Horizontal gene transfer between microorganisms enhances the non-healing tendency or chronic wound infections by polymicrobial organisms [24][25][26][27][28][29]. In the present study, we detected 18.8% of isolates showed multi-drug-resistance against at least five antimicrobial agents; in particular, the species involved were E. coli, K. pneumoniae, P. aeruginosa, A. baumannii, Citrobacter species and frequently seen isolate was methicillin-resistant Staphylococcus but not multi-drugresistant.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…P. rettgeri showed earlier sensitivity to antibiotics like ciprofloxacin, cephalosporin, carbapenems and amoxicillinclavulanate. However, emerging resistance to ciprofloxacin has been reported among Providencia species with a shift in sensitivity pattern from 100% to 46% in a study carried out by Fass RJ et al [16][17][18]. In our case series, we isolated multi-drug-resistant strains of P. rettgeri showed resistance to piperacillin-tazobactam, cefuroxime, ceftriaxone, cefepime, ertapenem, imipenem, meropenem, gentamicin, tobramycin, ciprofloxacin, tigecycline, amikacin, colistin and sensitive only to fosfomycin.…”
Section: The Management Of All Casesmentioning
confidence: 50%